Extension of chronological lifespan in Schizosaccharomyces pombe. (12th May 2021) - Ohtsuka, Hokuto; Shimasaki, Takafumi; Aiba, Hirofumi
Abstract: There are several examples in the nature wherein the mechanism of longevity control of unicellular organisms is evolutionarily conserved with that of higher multicellular organisms. The present microreview focuses on aging and longevity studies, particularly on chronological lifespan (CLS) concerning the unicellular eukaryotic fission yeast Schizosaccharomyces pombe . In S. pombe, >30 compounds, 8 types of nutrient restriction, and >80 genes that extend CLS have been reported. Several CLS control mechanisms are known to be involved in nutritional response, energy utilization, stress responses, translation, autophagy, and sexual differentiation. In unicellular organisms, the control of CLS is directly linked to the mechanism by which cells are maintained in limited‐resource environments, and their genetic information is left to posterity. We believe that this important mechanism may have been preserved as a lifespan control mechanism for higher organisms. Abstract : This microreview focuses on aging and longevity studies, particularly chronological lifespan (CLS), concerning the unicellular eukaryotic fission yeast ( Schizosaccharomyces pombe ). In S. pombe, over 30 compounds, 8 types of nutrient restriction, and over 80 genes that extend CLS have been reported.